PROSEDUR PEMBERIAN PEMBIAYAAN BSI KUR (KREDIT USAHA RAKYAT) SEBAGAI BENTUK MANAJEMEN RISIKO PEMBIAYAAN PADA BSI KCP GUDANG GARAM KEDIRI - Irtiqouli'ulya , Pandu; Yazid, Muhammad (Jurnal Dinamika Ekonomi Syariah, 2024)
This research aims to analyze the procedures for providing KUR (People's Business Credit) financing and financing risk management at BSI KCP Gudang Garam Kediri as a form of financing risk management. A qualitative approach was used with data collection techniques in the form of interviews and document studies. The research results show that BSI KCP Gudang Garam Kediri has structured financing procedures and fairly mature risk management. However, there is still a need for in-depth evaluation of the conformity of procedures with sharia principles, increasing the effectiveness of risk management, and increasing transparency and communication with potential borrowers. Research recommendations include the use of technology, partnership development, continuous monitoring and evaluation, and lending empowerment to improve and improve procedures for providing KUR financing. In conclusion, continuous improvements in procedures for providing financing and risk management can strengthen the position of BSI KCP Gudang Garam Kediri in supporting the sustainable growth and development of MSMEs, while still complying with sharia principles.